Exergy and energy comparison of organic phase change materials based thermal energy storage system integrated with engine exhaust - Yadav C.; Sahoo R.R. (My University, 2025)
In the present study, organic PCM based thermal energy storage system integrated with the engine exhaust system is investigated. Energy and exergy analysis of three organic PCMs namely lauric acid, stearic acid, and paraffin wax for various mass fractions have been performed. The present analysis provides a more realistic assessment than the conventional energy analysis approach. Parameters like charging efficiency, availability, energy, and exergy efficiencies are calculated based on thermodynamic laws. Also, this work is further extended to the energy and exergy saved for the integrated system with a various mass fraction of organic PCMs. The results revealed that lauric acid PCM based thermal energy storage has higher energy and exergy efficiency compared to paraffin wax and stearic acid PCMs. Lauric acid PCM provides 68% and 43.71% higher energy compared to stearic acid and paraffin wax PCMs, respectively. Also, a 0.4 kg mass fraction lauric acid has 57.5% and 37.25% higher exergy efficiency compared to stearic acid and paraffin wax PCMs integrated with engine exhaust. However, the energy and exergy efficiency of charging for paraffin wax PCM decreases with increase in mass fractions while the reverse effect occurred for stearic acid PCM. Thus, lauric acid at higher mass fraction is recommended for better thermal storage due to its lower charging time compared to stearic acid and paraffin PCMs. © 2019 Elsevier Ltd